(untitled) (XXI Century. Spanish Literature and Culture, 2024)
This article aims to offer an overview of Juan Mayorga’s theater and a synthesis of the constants of his dramatic production. First, we will analyze the playwright’s notions about theater and culture. Secondly, we will discuss the most recurring themes of his production, based on three dialectics: culture-barbarism, friend-enemy, word-silence. Finally, we will explain the predilected form of Mayorga’s plays: formally, they recognize themselves within the limits of the theatricality of Aristotelian roots, but embrace elements of postmodernity and epic-Brechtian theater, forming a "postmodern dramatic" theater.